An enantioselective synthesis of the C3–C21 segment of the macrolide immunosuppressive agent FR252921. Issue 26 (29th June 2016) - Ghosh, Arun K.; Rodriguez, Samuel
Graphical abstract: Highlights: Synthesis of the C3–C21 segment of the immunosuppressant FR252921 is achieved. The C12 and C13 chiral centers were set by a diastereoselective non-aldol process. Non-aldol route includes, alkylation, oxa-Michael reaction, and ring opening. The C18 stereogenic center was installed using Braun's acetate aldol reaction. Chiral reduction of β-keto-ester with NaBH4 and tartaric acid was investigated. Abstract: An enantioselective synthesis of the C3–C21 segment of the novel immunosuppressant FR252921 is described. The C12 and C13 stereogenic centers were constructed by a non-aldol process utilizing optically active 4-phenylbutyrolactone. The C18 stereogenic center was installed using Braun's highly diastereoselective acetate aldol reaction. Other key steps involved Curtius rearrangement and Horner–Wadsworth–Emmons olefination reactions.